FORMAÇÃO IMEDIATA DE ESPECIALISTAS EM INSTALAÇÕES ELÉTRICAS PARA A INDÚSTRIA NACIONAL DE ÓLEO E GÁS: O DESAFIO DOS PRÓXIMOS ANOS - do Amaral Pereira, Wilton Ney; Rando, Ricardo (Revista Ciências Exatas, 2013)
For legal demand: project, construction, assembly and maintenance of the electric facilities in industrial plants of oil and gas is qualified professionals' exclusive attribution. The formation, next years, of human resources legally qualified for this industrial segment is one of the main obstacles to the national dream exploration project of the prior-salt petroleum reserves. The current Brazilian system of education, as much public as private, besides the lamentable results reached in the last decade, doesn't have agility to answer, in quality and time, this demand. This article presents some alternatives for this impasse.